2010
DOI: 10.1186/1756-3305-3-44
|View full text |Cite
|
Sign up to set email alerts
|

Co-infections with Plasmodium falciparum, Schistosoma mansoni and intestinal helminths among schoolchildren in endemic areas of northwestern Tanzania

Abstract: BackgroundMalaria, schistosomiasis and intestinal helminth infections are causes of high morbidity in most tropical parts of the world. Even though these infections often co-exist, most studies focus on individual diseases. In the present study, we investigated the prevalence of Plasmodium falciparum-malaria, intestinal schistosomiasis, soil-transmitted helminth infections, and the respective co-infections, among schoolchildren in northwest Tanzania.MethodsA cross sectional study was conducted among schoolchil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
62
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 34 publications
(63 reference statements)
22
62
5
Order By: Relevance
“…Contrary to findings from field epidemiological studies, this study observed a low prevalence of S. mansoni (5.6%). Prevalence between 64% and 68% have recently been reported (Standley et al, 2010;Mazigo et al 2010b). The prevalence of E. histolytica/ E. dispar and G. lamblia reported in the present study was similar to that reported from Cameroon (Mbuh et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Contrary to findings from field epidemiological studies, this study observed a low prevalence of S. mansoni (5.6%). Prevalence between 64% and 68% have recently been reported (Standley et al, 2010;Mazigo et al 2010b). The prevalence of E. histolytica/ E. dispar and G. lamblia reported in the present study was similar to that reported from Cameroon (Mbuh et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…The trend of increasing prevalence of helminths with age observed in this study has been previously reported by other workers in the region Mazigo et al, 2010b). However, it was different from the normal U-shaped curve reported from a study by Kurup et al (2010).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The prevalence of asymptomatic malaria among patients was 16.4%, which was higher than that recently reported in school children in Tanzania (Nzobo et al, 2015). This is almost similar to the previous study in school children in a nearby place, which was 14.3% (Mazigo et al, 2010). In different parts of Africa, the prevalence of asymptomatic malaria varies considerably and prevalence up to 80% was reported in Cameroon (Okell et al, 2012).…”
Section: Prevalence Of Malaria By Mrdtcontrasting
confidence: 41%